2014
DOI: 10.1136/bmjopen-2013-004580
|View full text |Cite
|
Sign up to set email alerts
|

Associations between objectively assessed and self-reported sedentary time with mental health in adults: an analysis of data from the Health Survey for England

Abstract: ObjectiveThere is increasing interest in the association between sedentary behaviour and mental health, although most studies have relied solely on self-reported measures, thus making results prone to various biases. The aim was to compare associations between objectively assessed and self-reported sedentary time with mental health in adults.SettingCommunity dwelling population sample drawn from the 2008 Health Survey for England.Participants11 658 (self-report analysis) and 1947 (objective data) men and women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 33 publications
6
83
3
1
Order By: Relevance
“…In our study, women had higher time for both objectively measured and self-reported SB, but no statistical differences were observed versus men. These results showed that objectively measured time spent in SB in Chilean adults is comparable to that shown in adults from England (Hamer, Coombs, & Stamatakis, 2014). Self-reported time spent in SB (Table 1) showed similar results to those found with a similar question from the IPAQ in other South American countries such as Brazil and Colombia (Bauman et al, 2011), but lower than those reported in the United States (Cleland et al, 2014;Harrington, Barreira, Staiano, & Katzmarzyk, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…In our study, women had higher time for both objectively measured and self-reported SB, but no statistical differences were observed versus men. These results showed that objectively measured time spent in SB in Chilean adults is comparable to that shown in adults from England (Hamer, Coombs, & Stamatakis, 2014). Self-reported time spent in SB (Table 1) showed similar results to those found with a similar question from the IPAQ in other South American countries such as Brazil and Colombia (Bauman et al, 2011), but lower than those reported in the United States (Cleland et al, 2014;Harrington, Barreira, Staiano, & Katzmarzyk, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Sedentary behaviour is negatively associated with mental well-being39/health 40 41. Depression is a common form of mental distress.…”
Section: Discussionmentioning
confidence: 99%
“…cancer, chronic obstructive pulmonary disease (COPD), liver disease, renal disease, and arthritis; difficulties with activities of daily living (ADLs, no difficulties at all vs. some or great difficulties); depressive symptoms assessed by the 15-item Geriatric Depression Scale (GDS) using cutoff of 5 (no vs. yes), (Brink et al 1982;Yesavage and Sheikh 1986); mean daily accelerometer wear time (Hamer et al 2014), and baseline AD8 scores.…”
Section: Covariatesmentioning
confidence: 99%